SCHRÖDINGER'S PLOT, REVISITED: QUANTUM INDETERMINACY AND NON-DETERMINISTIC NARRATIVE IN CONTEMPORARY SCIENCE FICTION - Salwa K.M (PEOPLE: International Journal of Social Sciences, 2025)
The enduring interplay between scientific paradigms and literary expression continues to shape our understanding of reality and narrative. While classical literary analysis often presupposes deterministic plot trajectories and clear causal chains, the revolutionary insights of quantum mechanics have introduced fundamental indeterminacy into our understanding of the universe. This paper argues that the conceptual framework of quantum indeterminacy, as initially explored in Modernist "quantum poetics" by figures like Daniel Albright, has profoundly influenced the non-deterministic plot progression and ambiguous narrative closure characteristic of contemporary science fiction, particularly in narratives featuring highly autonomous artificial intelligence. Drawing on the philosophical implications of quantum theory, as articulated by thinkers like Carlo Rovelli and Slavoj Žižek, this study has analyzed how select works of contemporary science fiction particularly the trending Murderbot Diaries construct plots that resist singular, predictable outcomes, mirroring the inherent probabilistic nature of quantum reality. By examining the manifestation of quantum indeterminacy in narrative structure, this paper seeks to illuminate the sophisticated engagement of modern science fiction with cutting-edge scientific and philosophical thought, contributing to the interdisciplinary dialogue between literature and science.